A novel chaotic system and its topological horseshoe - Li, Chunlai; Wu, Lei; Li, Hongmin; Tong, Yaonan (Nonlinear Analysis: Modelling and Control, 2013)
Based on the construction pattern of Chen, Liu and Qi chaotic systems, a new threedimensional (3D) chaotic system is proposed by developing Lorenz chaotic system. It’s found that when parameter e varies, the Lyapunov exponent spectrum keeps invariable, and the signal amplitude can be controlled by adjusting e. Moreover, the horseshoe chaos in this system is investigated based on the topological horseshoe theory.